MENGUNGKAP KEBERADAAN FIKIH: KEBENARAN RELATIF YANG DIANGGAP ABSOLUT - Defel Fakhyadi (TAHKIM, 2017)
This article proves that fiqh is a form of understanding of a person in understanding the meaning contained in the Qur'an and Sunnah. Fiqh is an intellectual property in understanding Islamic law so that the existence of jurisprudence must be in accordance with the development of the times and human needs. The sacrality to fiqh is something wrong because fiqh is an understanding of the voluntary law. The development of jurisprudence can reach the golden age if the ulama are open to criticism, not the madhhab fanaticism and always reform Islamic law so that Islamic law will be easy to absorb in life and society life. Responsive and conditional Islamic law is a legal aspiration desired by the shari'ah because the principle of sharia is the achievement of the benefit of the umma (maqasid shari'ah)